Unintentional injuries in children at pediatric emergency center: A developing country perspective - Choudhary, Bharat; Choudhary, Yachana; Gupta, Suresh (Indian Journal of Child Health, 2017)
Background: Unintentional injuries are important cause for childhood mortality and long-term morbidity. Developing countries accounts for majority of the childhood deaths due to unintentional injuries. Methods: This was a retrospective descriptive study done at a tertiary care center. Data were obtained from the records of patients. Result: A total of 180 children presented to pediatric emergency during the study period with male-to-female ratio of 2.1:1. The injuries were more common in 1-5-year age group. The most common mechanism of injuries were fall (49.4%) and hit by object (11.1%). Most of the injuries occurred at home. Median duration of arrival to hospital was 60 minutes. Out of 180 children, 19 (10.5%) required hospital admission. Injuries over the head and face were significantly associated with hospital admissions (adjusted odds ratio: 6.45, 95% confidence interval: 1.96-21.93, p=0.002).Background: Unintentional injuries are important cause for childhood mortality and long-term morbidity. Developing countries accounts for majority of the childhood deaths due to unintentional injuries. Methods: This was a retrospective descriptive study done at a tertiary care center. Data were obtained from the records of patients. Result: A total of 180 children presented to pediatric emergency during the study period with male-to-female ratio of 2.1:1. The injuries were more common in 1-5-year age group. The most common mechanism of injuries were fall (49.4%) and hit by object (11.1%). Most of the injuries occurred at home. Median duration of arrival to hospital was 60 minutes. Out of 180 children, 19 (10.5%) required hospital admission. Injuries over the head and face were significantly associated with hospital admissions (adjusted odds ratio: 6.45, 95% confidence interval: 1.96-21.93, p=0.002). Conclusion: Pediatric injuries are common in India. Male children are at higher risk. Injuries over the head and face are associated with higher rates of hospitalization in children. Pediatric injuries are common in India. Male children are at higher risk. Injuries over the head and face are associated with higher rates of hospitalization in children.